Neutrophil-to-lymphocyte ratio as a prognostic marker in acute respiratory distress syndrome patients: a retrospective study - Wang, Ying; Ju, Mohan; Chen, Cuicui; Yang, Dong; Hou, Dongni; Tang, Xinjun; Zhu, Xiaodan; Zhang, Donghui; Wang, Lilin; Ji, Shimeng; Jiang, Jinjun; Song, Yuanlin (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Acute respiratory distress syndrome (ARDS) is the leading cause of high mortality in intensive care units (ICUs) worldwide. An effective marker for prognosis in ARDS is particularly important given the absence of effective treatment strategies aside from small tidal volume ventilation. Previous studies identified an association between the neutrophil-to-lymphocyte ratio (NLR) and prognosis in critical patients. In this study, we explored the prognostic and predictive value of the NLR in ARDS patients. Methods: We retrospectively included 275 ARDS patients treated at a single institute from 2008 to 2015. After excluding patients with chronic lung disease, acute myocardial infarction and missing data, 247 patients were ultimately included in the analysis. Clinical characteristics and experimental test data, including the NLR, were collected from medical records at 24 hours after the ARDS diagnosis. Independent prognostic factors were determined by multivariate Cox regression analysis. Subgroup stratification was performed according to different factors, and the continuous factors were divided according to the median values. Results: The NLR in survivors was significantly lower than that in non-survivors (P14) and a low NLR group (NLR ≤14). We found that an NLR >14 was associated with a shorter overall survival (OS) (P=0.005). In the multivariate Cox regression model, we further identi ed an NLR >14 as an independent prognostic factor for OS [hazard ratio (HR) 1.532, (95% CI, 1.095–2.143), P=0.013]. Subgroup analysis showed that the prognostic value of the NLR was higher in hypertensive patients (P=0.009) and in patients with low red blood cell speci c volume (P=0.013), high sodium (P=0.002) and high creatinine levels (P=0.017). Conclusions: The NLR is potentially a predictive prognostic biomarker in ARDS patients.